Prevalence and clinical determinants of community-acquired legionella pneumonia in immunocompetent adults in a University Hospital - Alejandria, Marissa M. (Thesis -- (MS in Clinical Epidemiology), College of Medicine)
Background: Lack of rapid reliable test for the etiologic diagnosis of atypical pneumonia limits the accuracy of prevalence studies on atypical pathogens in community-acquired pneumonia (CAP). Among the atypical pathogens, Legionella pneumonia is associated with a more severe clinical course than Mycoplasma or Chlamydia infection. This current treatment guidelines recommend empiric coverage for atypical agents despite the lack of studies on the burden of disease, epidemiologic and clinical features of atypical pathogens in hospitalized CAP patients in the Philippines. RESULTS: Out of 286 patients screened, 227 patients with moderate and high risk CAP were included. The overall prevalence of atypical pathogens was 34% (95% CI 28%, 40%) with Legionella as the predominant atypical pathogen. Based on a four-fold antibody rise and/or positive urine antigen, 39 patients (17.2%; 95% CI and 12.5%, 22.7%) had Legionella pneumonia. Of these, Legionella was found mainly as a co-pathogen with other bacterial organisms in 34 patients and as a sole pathogen in five patients only. Mycoplasma pneumoniae was seen in 12.3% and Chlamydophila pneumoniae in 12.7% of the patients, mainly as co-pathogens. Non-atypical organisms were isolated as the sole pathogen in 91 (40%) patients with Streptococcus pneumoniae. Hemophilus influenzae and Klebsiella as the common bacterial pathogens. Mixed atypical and bacterial pathogens were identified in 55 (24.2%) patients. No etiologic agent was identified in 36 patients (16%). The overall mortality was 25% with a 5% case fatality rate for Legionella pneumonia. On multivariable analysis, only age <40 years old [aOR 5.4; 95% CI 1.8, 16.8], history of chronic alcoholism [aOR 3.0; 95% CI 1.1, 8.9] were independently associated with Legionella pneumonia. None of the co-morbid condition signs and symptoms and laboratory findings was found to be associated with Legionella pneumonia. CONCLUSION AND RECOMMENDATIONS: In hospitalized patients with CAP, atypical pathogens were fairly common occurring either as the sole pathogen or as a co-pathogen with bacterial organism in 34% of the study population. Legionella was the predominant atypical pathogen in 17% of CAP patients. There was a paucity of factors found to be associated with Legionella pneumonia. However, the study was underpowered to conclude definitively that there are no differentiating characteristics between Legionella and bacterial pneumonia. The high frequency of atypical pathogens, particularly Legionella, plus the minimal incremental cost accrued with the use of empiric antibiotic regimens with coverage for atypical pathogens provide evidence to support the current treatment guidelines for CAP. Erythromycin, the newer macrolides and extended-spectrum fluoroquinolones are the antibodies active against atypical pathogens, which can be included in the empiric antibiotic regimens for moderate to high-risk CAP patients in the absence of rapid accurate diagnostic test for atypical pathogens. This recommendation, however, does not take into consideration efficacy rates and long-term ecologic effects of empiric antibiotic regimens. A well-designed randomized controlled trial is needed to establish the cost-effectiveness of empiric coverage for atypical pathogens versus targeted therapy. Accurate and rapid diagnostic tests for atypical pathogens also need to be developed.
Available to the General Public.
Keywords: Pneumonia, Lobar; Pulmonary Inflammation